Carbon nanotubes@metal–organic frameworks as Mn-based symmetrical supercapacitor electrodes for enhanced charge storage1. Issue 72 (6th August 2015) - Zhang, Yidong; Lin, Baoping; Sun, Ying; Zhang, Xueqin; Yang, Hong; Wang, Junchuan
<x xml:space="preserve">Abstract</x> A hybrid material of carbon nanotubes (CNTs) and Mn-based metal organic frameworks (Mn-MOF) was synthesized and used as a Mn-based supercapacitor electrode material.